ELECTRONIC REGISTER OF MEDICAL SICK-LIST IT’SA METHODS TOWARD CORRUPTION STRUGGLE - Tkachenko, P.I.; Korotich, E.; Korotich, N.; Vashchenko, I. (World of Medicine and Biology, 2012)
The article is devoted to the electronic register of sick-list and it order of application in the medical practice. The difficulties are emerged during its implementation. The authors formed their own point of view connected with possible variants of their decision and introduction of the register.
Keywords: electronic register; sick-list; physician; medical establishment